A STUDY ON RELATION BETWEEN STUDY HABITS AND PERSONALITY TRAITS OF HIGHER SECONDARY STUDENTS - Sheebha, Nuvetha (International Journal of Research -GRANTHAALAYAH, 2016)
Acquiring five years of general education, at the higher secondary level, the students are focused to a diversification of subjects. Hence, they automatically develop into students following certain new study habits, which suit their change in the academic field. Many students undergo private tuition to improve their performance, but this improvement cannot be achieved overnight. What they need is improvement in studies by various ways and means. This can be achieved only by means of having proper and regular study habits.